Challenges in diagnosing familial Mediterranean fever: exploring atypical clinical features. Clinical case - Maria V. Barsuk; Alexander V. Novikov; Tamara A. Mikhalina; Vilen V. Rameev; Lidia V. Lysenko (Терапевтический архив)
This clinical case series presents descriptions of 3 patients with familial Mediterranean fever (FMF) who have atypical manifestations and abnormal inheritance mechanisms in terms of Gregor Mendel's laws. Although molecular genetic testing can help with disease diagnosis, it is not always conclusive. The primary need for genetic testing in atypical cases is to explain the mechanism of inflammation and to select the optimal therapy. These clinical observations demonstrate the changes in the spectrum of phenotypic manifestations of FMF in the context of the widespread introduction of molecular genetic methods.